Herpes Zoster Ophthalmicus Presenting with Suspected Orbital Myositis Following Recent Recombinant Zoster Vaccination - Muhammad Awan; Musa Azhar; Mujtaba Khan; Ali Qureshi; Fawaz Qazi; Dawood Hafeez; Jeffrey Sheridan (Journal of Ophthalmic Science, 2026)
Herpes zoster ophthalmicus (HZO) is a manifestation of varicella-zoster virus (VZV) reactivation involving the ophthalmic division of the trigeminal nerve, carrying significant risk of vision-threatening complications. Diplopia in HZO is often attributed to cranial nerve palsy, although orbital myositis remains a rare and underrecognized cause. We present a 79-year-old male who developed right-sided headache, binocular diplopia, and a V1 vesicular rash two weeks after receiving the recombinant zoster vaccine. Examination revealed restriction of extraocular movements without a localizing cranial nerve pattern, raising suspicion for orbital myositis. Neuroimaging was unremarkable, and VZV polymerase chain reaction confirmed the diagnosis of HZO. The patient received antiviral therapy and was discharged in stable condition after three days. This case highlights HZO presenting with suspected orbital myositis in temporal association with vaccination and underscores the need for vigilance for uncommon neuro-ophthalmic manifestations, as early recognition and treatment are essential to prevent vision-threatening complications. Given the patient's advanced age, this case also emphasizes the possibility that age-related immunosenescence may contribute to VZV reactivation and the development of HZO-related ocular complications. Potential therapeutic approaches targeting age-related immune dysfunction are also considered.
Keywords: Herpes zoster ophthalmicus